2017
DOI: 10.3897/zookeys.682.12670
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genus Capoeta Valenciennes, 1842 from the Caspian Sea basin in Iran (Teleostei, Cyprinidae)

Abstract: A new species of algae-scraping cyprinid of the genus Capoeta Valenciennes, 1842 is described from the Kheyroud River, located in the southern part of the Caspian Sea basin in Iran. The species differs from other members of this genus by a combination of the following characters: one pair of barbels; predorsal length equal to postdorsal length; maxillary barbel slightly smaller than eye’s horizontal diameter and reach to posterior margin of orbit; intranasal length slightly shorter than snout length; lateral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…The value of mean expected heterozygosity are lower compared to the population of Capoeta capoeta gracilis from Madarsu and Gorganrud rivers from north part of Iran (Aliakbarian et al (2014), but are higher than those found in rivers of Golestan Province of Iran for Spirlin (Alburnoides bipunctatus) (Jahangiri et al 2013). Similar observations on heterozygosity range were reported for other cyprinid fishes ((Jouladeh-Roudbar et al 2017). Our values are also comparable with those found for the common carp from southeastern part of Caspian Sea and for Capoeta trutta populations from two main watersheds in the Kurdistan province (Mirzaei et al 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The value of mean expected heterozygosity are lower compared to the population of Capoeta capoeta gracilis from Madarsu and Gorganrud rivers from north part of Iran (Aliakbarian et al (2014), but are higher than those found in rivers of Golestan Province of Iran for Spirlin (Alburnoides bipunctatus) (Jahangiri et al 2013). Similar observations on heterozygosity range were reported for other cyprinid fishes ((Jouladeh-Roudbar et al 2017). Our values are also comparable with those found for the common carp from southeastern part of Caspian Sea and for Capoeta trutta populations from two main watersheds in the Kurdistan province (Mirzaei et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…However little level of genetic distinctiveness in Kharsan and Beshar River could be related high migration rate of this species. The species' life history also plays a role in influencing contemporary levels of spatial population structure (Jouladeh-Roudbar et al 2017;Bilici et al 2017). These data and limited information on C. aculeata suggest that C. aculeata adult habitat is distinctive within the river systems they use for spawning.…”
Section: Discussionmentioning
confidence: 99%
“…The LWRs recorded for all three species, covering two new maximum lengths. The new TL max for C. coadi is substantial 33.3 cm compared to 19.5 cm and a similarly high new TL max is now recorded for C. pyragyi as 33.8 cm instead previous report of 15.6 cm (Jouladeh‐Roudbar, Eagderi, Ghanavi, & Doadrio, ). The intercept (a) values indicated a fusiform body shape for all three species (Froese, ).…”
Section: Discussionmentioning
confidence: 43%
“…Out of twenty-one Anatolian Capoeta species, six are cross-border (C. barroisi, C. capoeta, C. damascina, C. trutta, C. umbla and C. ekmekciae), fifteen are endemic to Turkish freshwater fauna (C. angorae, C. antalyensis, C. aydinensis, C. baliki, C. banarescui, C. bergamae, C. kosswigi, C. caelestis, C. erhani, C. mauricii, C. oguzelii, C. pestai, C. sieboldii, C. tinca and C. turani). Recent morphological studies (Turan et al, 2006a;Turan et al, 2006b;Turan et al, 2008;Turan et al, 2017;Elp et al, 2018) and molecular studies on the Capoeta genus (Turan, 2008;Bektaş, Çiftçi, Eroğlu, & Beldüz, 2011;Levin et al, 2012: Geiger et al, 2014Alwan, Zareian, & Esmaeili, 2016;Ghanavi, Gonzalez, & Doadrio, 2016;Jouladeh-Roudbar, Eagderi, Ghanavi, & Dadrio 2017;Zareian, Esmaeili, Heidari, Khoshkholgh, & Mousavi-Saber, 2016) to resolve taxonomic uncertainties caused by phenotypic plasticity (Berg, 1949;Banarescu, 1999;Doadrio & Madeira, 2004) have led to an increase in the number of species indicating that the taxonomy of the Capoeta species group has not yet been fully resolved. Recently, Bektaş et al (2017) has been genetically defined Anatolian Capoeta species with a extensive molecular research using cyt b gene sequences.…”
Section: Introductionmentioning
confidence: 99%